Quantum Interference in Mixed‐Valence Complexes: Tuning Electronic Coupling Through Substituent Effects. Issue 45 (11th October 2022) - Harrison, Daniel P.; Grotjahn, Robin; Naher, Masnun; Ghazvini, Seyed M. B. H.; Mazzucato, Daniel M.; Korb, Marcus; Moggach, Stephen A.; Lambert, Colin; Kaupp, Martin; Low, Paul J.
Abstract: Whilst 2‐ or 5‐OMe groups on the bridging phenylene ring in [Cp*(dppe)RuC≡C2 (μ‐1, 3‐C6 H4 )] + have little influence on the electronic structure of this weakly coupled mixed‐valence complex, a 4‐OMe substituent enhances ground state electron delocalization, and increases the intensity of the IVCT transition. Vibrational frequency and TDDFT calculations (LH20t‐D3(BJ), def2‐SVP, COSMO (CH2 Cl2 )) on ([Cp*(dppe)RuC≡C2 (μ‐1, 3‐C6 H3 ‐n‐OMe)] + ( n =2, 4, 5) models are in excellent agreement with the experimental results. The stronger ground state coupling is attributed to the change in composition of the β‐HOSO brought about by the 4‐OMe group, which is ortho or para to each of the metal fragments. The intensity of the IVCT transition increases with the greater overlap of the β‐HOSO and β‐LUSO, whilst the relative phases of the β‐HOSO and β‐LUSO in the 4‐OMe substituted complex are consistent with predictions of constructive quantum interference from molecular circuit rules. Abstract : The degree of ground state electronic interaction in the mixed‐valence complex [Cp*(dppe)RuC≡C2 (μ‐1, 3‐C6 H4 )] + can be tuned through the introduction of an OMe substituent to the bridging ligand. These effects are sensitive to the position of the substituent, and follow the same patterns as those predicted by quantum circuit rules for weakly coupled molecules in molecular junctions.